Tri-axial tests for brittle materials: motivation, technique, results = Badanie materiałów kruchych w stanie trójosiowym: motywacja, technika badań, wyniki - Litewka, Andrzej; Szojda, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the paper is to explain the experimental technique used in tri-axial material tests and to supply new and more general experimental data on deformability and fracture of ceramics and cementitious composites. Such experimental data are necessary to formulate theoretical models capable to describe the mechanical behaviour of brittle rocklike materials. The program of experiments consisted of two different tests performed under tri-axial loading and also of uni-axial compression that supplied preliminary data necessary to calibrate the material. The second objective of this study is to present the potentialities of own phenomenological model based on continuum damage mechanics and on theory of tensor function representation that can be used to describe the response of brittle rock-like material subjected to tri-axial state of stress.
Keywords: materiały konstrukcyjne; materiały kruche; mechanika materiałów; experimental methods; triaxial tests; rock-like brittle materials; stresses at fracture